Elastography detected solid organ stiffness increased in patients with acromegaly. Issue 3 (January 2019) - Bankir, Mehmet; Sumbul, Hilmi Erdem; Koc, Ayse Selcan; Demirtas, Derya; Acibucu, Fettah
Abstract : Abstract: Elastography is a method to examine the increase in solid organs stiffness (SOS), and there is no data in the literature regarding to its use in patients with acromegaly. In this study, we aimed to investigate the change of SOS in patients with acromegaly and to determine the parameters closely related to SOS in same patient groups. We included 40 subjects with acromegaly and 40 healthy control subjects. In addition to routine renal, liver and thyroid ultrasonography (USG), SOS for 3 solid organs were measured by elastography. The participants of the study were divided into 3 groups as the control (Group-I), acromegaly patients with remission (Group-II), and acromegaly patients without remission (Group-III). Insulin growth factor-1 (IGF-1) level significantly increased from Group-I to Group-III. Glucose, creatinine, albuminuria, alkaline phosphatase, TSH, and growth factor levels were highest in Group-III and statistically significance was found only between Group-I and Group-III. Liver, kidney and thyroid size and echogenicity were increased from Group-I to Group-III. Liver and renal stiffness and thyroid gland strain ratio significantly increased from Group-I to Group-III and these parameters were statistically different between all groups. In linear regression analysis, IGF-1 levels were independent determinants of SOS. SOS values of acromegaly patients with active disease were significantly increased compared to both the control group and the acromegaly patients in remission phase. Serum IGF-1 levels were independently associated with SOS in these patients. SOS measurement should be part of a routine USG examination in patients with acromegaly, especially in patients during active disease.